Primary corneal endothelial degeneration in dogs retrospectiive study of 30 cases - Miranda, Rita Cacho (2022)
Primary corneal endothelial degeneration (CED) is manly an age-related condition, characterized by a slow progression, that presents a breed predisposition in different canine breeds like Chihuahuas, Boston Terriers and Dachshunds, and is more common in females. Several surgical procedures are described to decrease the degree of corneal oedema and to help with the resolution of the ulcers. The objective of this study was to conduct a retrospective investigation of canine CED, in order to characterize the clinical presentation of the disease, to evaluate potential risk factors and to analyse response to different surgical approaches. Thirty dogs with CED presented to the ROWE Referrals Eye Clinic, Bradley Stoke, United Kingdom, between January 2016 and March 2019, with ages ranging from 3 to 14 years (mean 9.8 ± 2.7 years), were enrolled in this research. The studied population was composed mainly by females (n=19; 63.3%), and included dogs from 11 different breeds, with Shih-Tzus (n=7, 23.3%), Boston Terriers (n=4, 13.3%), Italian Spinones (n=4, 13.3%), and Jack Russel Terriers (n=3, 10.0%) being the most represented; and two cross-breed dogs. Most dogs presented a diffuse (46.7%, n =14) or focal corneal oedema (30.0%, n= 9). Twenty-four dogs were submitted to surgical procedures, mainly Diamond burr (n=11, 45.8%) and grid keratotomy (n=5; 20.1%). According to the tutor´s perception, the Gunderson flap and corneal transplant were the surgical techniques with a better visual outcome.